Perjanjian Perkawinan Sebagai Perlindungan Hukum Terhadap Harta Bersama Akibat Perceraian - Ni Kadek Ani; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2021)
In living a household life, it is often that problems arise that cause disputes and end up with divorce between couples. The breakup of marriage will cause problems, one of which is the family's wealth. Marriage agreements are made to anticipate possible problems that occur in a marriage. The problem statement from this study is: (1) how is the arrangement of the Marriage Law in Law Number 1 of 1974 concerning Marriage? (2) How is the legal protection of common property after the verdict of the Constitutional Court Number 69/PUU-XIII/2015 in the event of a divorce? This study is a type of normative law research, since its assessment is carried out through a library study. The Regulation of Marriage Agreements in Law Number 1 of 1974 concerning Marriage, contained in Chapter V, Article 29. The Marriage Agreement was made before the marriage was held and valid since the marriage took place. After the verdict of the Constitutional Court Number 69/PUU-XIII/2015, the Marriage Agreement can be made after the marriage between the husband and wife takes place and must be recorded. This marriage agreement binds the husband, wife, and third party. Marriage agreements provide law protection for both husband and wife to their property if they have to divorce for a reason.